(untitled) (Journal of Dhaka Medical College, 2015)
Hydatid disease is a parasitic disease, which is most commonly caused by Echinococcus granulosus. It is endemic in many parts of the world. However, Hydatid disease can occur in almost any part of the body. Isolated omenal hydatid cyst is one of the least common sites. A case of very unusual omental hydatid cyst is presented here which was diagnosed in the Department of Radiology & Imaging, Dhaka Medical College Hospital, Dhaka, and subsequently confirmed by histopathology. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21546 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 216-218